Strengthening Oversight by Legislatures - World Bank (Washington, DC, 2012)
About 90 percent of the world's nearly 200 sovereign states have national legislatures or parliaments. With the spread of democracy and the rise of multiparty political systems, these bodies are playing larger roles in government. Increasingly, legislatures and their members perform four important functions of governance: Making policies and laws. Legislatures are representative bodies for collective decision-making, working with the executive branch to deliberate policies and make laws. Representing citizens. Legislators give voice to individual citizens, civil society organizations, and business groups, representing the needs of local constituents in policymaking. Overseeing the executive. Legislatures oversee policy implementation by the executive branch, scrutinizing its work and holding it accountable. Recruiting future leaders. Legislatures are stepping stones and training grounds for senior positions in the executive branch.